Предмет: Алгебра,
автор: блааааа
Упростить выражение:
1) 2 ( cosα + cos3α ) / 2sin2α + sin4α
2) 1 + sinα - cos2α - sin3α / 2sin²α + sinα - 1
Ответы
Автор ответа:
0
4*cos2α*sinα*cosα = 2 * (2*sinα *cosα) *cos2α = 2 * sin 2α * cos 2α = sin4α
(cosα + cos 3α) / (sin 3α - sinα) = 2*cos2α*cosα / 2*cos2α*sinα) = cosα / sinα = ctg α
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: Қазақ тiлi,
автор: aizora
Предмет: Алгебра,
автор: dmitrii23
Предмет: Химия,
автор: Grafova02